The new leaf loving dematiaceous taxa from Madhya Pradesh - and K.M. VYAS, C.D. SHARMA, A.N. RAI (Indian Phytopathology, 2002)
Two new interesting leaf spotting fungi, viz. Tripospermum fici sp. novo on Ficus sp. and T. lamiacearum sp. and novo on Colebrookiaoppositifolia Smith are described, illustrated and compared with allied species.